Eksistensi Filsafat Seni pada Era Disrupsi - Putu Ayu Ditha Zeptyani; Ida Ayu Made Yuni Andari; Ni Wayan Ria Lestari (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2023)
The era of disruption brings fundamental changes in the art world, presenting challenges and opportunities that require deep philosophical understanding. This research aims to explore the existence of art philosophy in the era of disruption, discussing the transformation of art identity, the dynamics of the relationship between art and technology, ethical considerations in digital art, the role of art as an agent of social change, and the shifting paradigm of the art economy. The results of this research provide an in-depth look at the complexities of contemporary art in the face of cultural, technological, and social change. The practical and philosophical implications of the existence of art philosophy are outlined, providing a foundation for artists, researchers, and art lovers to understand and permeate the dynamics of art in this time of disruption. This research also identifies future research directions to deepen the understanding of the role of philosophy of art in facing challenges and innovations in the evolving art world.